OPTIMASI EKSTRAK BIOAKTIF PROPOLIS MENGGUNAKAN MICROWAVE-ASSISTED EXTRACTION DENGAN RESPONSE SURFACE METHODOLOGY - Marthia, Nabila; Triani, Rini; M, Nur Annisa Fitriana (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
Propolis is a natural bee product rich in bioactive compounds such as flavonoids and phenols, which act as potent antioxidants and antimicrobials. This study aimed to optimize the extraction of propolis using the Microwave-Assisted Extraction (MAE) method through a Response Surface Methodology (RSM) approach and Central Composite Design (CCD). The independent variables were solvent volume (100–150 mL) and extraction time (5–8 min), while the responses measured included total flavonoids, total phenols, and antioxidant activity (IC₅₀). All responses followed a quadratic model with high coefficients of determination (R² > 0.9) and non-significant lack of fit. The optimum condition was achieved at 150 mL solvent volume and 6.5 min extraction time, with a desirability value of 0.98. Verification showed that experimental values fell within the 95% prediction interval, confirming the accuracy of the model. These results demonstrate that MAE is an efficient method for producing quality propolis extracts with strong biological potential.